The Blood-Brain Barrier as a Cause of Obesity - Banks, William A. (Current Pharmaceutical Design, 2008)
The dramatic increase in the number of obese and overweight persons has spurred interest in control of appetite, body weight, and adiposity. Leptin is the humoral component of a negative feedback loop between adipose tissue and brain. Leptin is secreted from fat in proportion to the degree of adiposity, is transported across the blood-brain barrier (BBB), and acts in the brain to decrease appetite and increase thermogenesis, actions that ultimately decrease adiposity. However, leptin fails as an adipostat because leptin resistance arises in obesity. The BBB transporter is the first part of the feedback loop to fail, producing the so called “peripheral resistance” to leptin. In this sense, obesity is a disease of the BBB. Failure of leptin as an adipostat raises the question of what its primary role is as does its effects on reproduction, bone, immunity, breathing, cognition, and neurogenesis. Kinetics analysis shows that the BBB transporter performs most efficiently at low serum levels of leptin, suggesting that the feedback loop evolved to operate at lower leptin levels than those seen in ideal body weight. We suggest that low levels of serum leptin inform the brain that adipose reserves are adequate to expend calories on functions other than feeding, such as reproduction and the immune system. This feedback loop is short-circuited when an animal enters starvation. Hallmarks of starvation include decreased secretion of leptin by adipose tissue and hypertriglyceridemia. Triglycerides inhibit the transport of leptin across the BBB, thus attenuating the leptin signal across the BBB and providing a mechanism for peripheral leptin resistance. Triglycerides are elevated in both starvation and obesity. We postulate that hypertriglyceridemia evolved as a starvation signal to the brain that acts in part to inhibit the transport of the leptin across the BBB. The hypertriglyceridemia of obesity invokes this aspect of the starvation response, inducing leptin resistance at the BBB. Thus, the BBB plays important roles in both obesity and starvation.